BEST SUSTAINABILITY PRACTICES WITH SUSTAINALYTICS: INSIGHTS FROM IDX ESG STAR COMPANIES - Breliastiti, Ririn; Andry, Johanes Fernandes; Lee, Francka Sakti; Nelson, Catheryn Iona (Jurnal Akuntansi Bisnis, 2025)
Background: In the rapidly evolving landscape of global finance, sustainability has become a critical factor influencing investment decisions and corporate strategies. The Indonesia Stock Exchange (IDX) has taken significant steps to integrate sustainability into its capital market, including its ESG Star program, which recognizes companies excelling in Environmental, Social, and Governance (ESG) performance. This research explores how Sustainalytics supports IDX ESG Star companies in driving sustainability practices and enhancing corporate accountability.Objective: By examining these companies’ best practices, the study aims to shed light on the effectiveness of ESG criteria in fostering sustainable development and market competitiveness.Research Methods: This study uses an exploratory and descriptive research design to analyze sustainability practices among IDX ESG Star companies based on Sustainalytics ratings. It employs secondary data collection, including ESG ratings, IDX criteria, and academic research. Data analysis combines qualitative and comparative methods to identify best practices and offer actionable recommendations.Research Results: The study reveals that the eight companies excel in environmental, social, and governance (ESG) practices. Environmentally, they focus on green buildings, renewable energy, and emissions reduction. Socially, they prioritize inclusivity, financial access, and employee well-being. Governance-wise, they adhere to transparent reporting and international standards, demonstrating strong ESG integration.Originality/Novelty of Research: This study offers a novel analysis by focusing on IDX ESG Star companies and their sustainability practices, using Sustainalytics ratings as a benchmark. It highlights best practices in environmental, social, and governance areas, providing actionable insights for companies to enhance their ESG performance and contributing to the broader sustainability discourse in Indonesia’s capital market.